Recent Publications (Quarterly Journal of Economics, 1968)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 82, Issue 4, November 1968, Pages 689–693, https://doi.org/10.1093/qje/82.4.689 Published: 01 November 1968